2021
DOI: 10.3390/rs13163129
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Forest Inventory Parameters with Apple iPad Pro and Integrated LiDAR Technology

Abstract: The estimation of single tree and complete stand information is one of the central tasks of forest inventory. In recent years, automatic algorithms have been successfully developed for the detection and measurement of trees with laser scanning technology. Nevertheless, most of the forest inventories are nowadays carried out with manual tree measurements using traditional instruments. This is due to the high investment costs for modern laser scanner equipment and, in particular, the time-consuming and incomplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 64 publications
5
54
0
1
Order By: Relevance
“…A LiDAR scanner ubiquitously available on consumer-grade devices was presented with the introduction of the iPad Pro 2020 11-inch and 12.9-inch display (hereafter iPad) on March 25, 2020 and the iPhone 12 Pro and iPhone 12 Pro Max (hereafter iPhone) on October 23, 2020 by Apple Inc.. Comparisons between the iPad LiDAR sensor, a hand-held personal laser scanning approach and traditional forest inventory equipment already demonstrated a high detection rate of tree stems above a threshold of 10 cm diameter 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…A LiDAR scanner ubiquitously available on consumer-grade devices was presented with the introduction of the iPad Pro 2020 11-inch and 12.9-inch display (hereafter iPad) on March 25, 2020 and the iPhone 12 Pro and iPhone 12 Pro Max (hereafter iPhone) on October 23, 2020 by Apple Inc.. Comparisons between the iPad LiDAR sensor, a hand-held personal laser scanning approach and traditional forest inventory equipment already demonstrated a high detection rate of tree stems above a threshold of 10 cm diameter 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…They derived the best DBH estimates using a direct least squares ellipsoid fitting algorithm on resultant point clouds. Gollob et al [68] found that DBH was underestimated for stems with DBH < 15 cm and overestimated with stems >30 cm. However, the DBH threshold where stems were over-or underestimated depended on the software used to pre-process the RGB-D information.…”
Section: Terrestrial Low-cost Depth Sensor Literature Analysismentioning
confidence: 99%
“…Of the identified literature, seven publications explored the application of RGB-D devices. Two of these studies were conducted at the individual stem scale [42,47] and four at the plot scale [43,55,68,69]. Only Fan et al [44] utilised an RGB-D sensor at both the individual stem and plot capture scales within the one study in order to best target different inventory measurements.…”
Section: Terrestrial Low-cost Depth Sensor Literature Analysismentioning
confidence: 99%
See 2 more Smart Citations